2015
DOI: 10.1002/cam4.416
|View full text |Cite
|
Sign up to set email alerts
|

Warburg effect regulated by amphiregulin in the development of colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the most frequently occurring cancers with high morbidity and mortality worldwide. Amphiregulin (AREG), a member of the epidermal growth factor family and a rational target for CRC therapy, is essential for the three-dimensional structure of tumor formation. To clone the genes associated with increased AREG expression, we performed a cDNA microarray analysis in two CRC cell lines undergoing two-dimensional (2DC) and three-dimensional culture (3DC). Upregulated (>2.0-fold) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 51 publications
3
34
0
Order By: Relevance
“…We therefore propose that the glucose-sensing transcription factor MLX and myokine signaling may encompass a novel part of the molecular pathway necessary for glucose-induced adaptive myogenesis. Given its widespread expression, MLX may modulate the transcription of secreted signaling proteins in response to glucose in many cell types, which was also implicated by a recent study in colorectal cancer cells (Nam et al 2015). Therefore, our study indicates that MLX has more diverse roles than previously anticipated, presumably in concert with the large network of positive and negative transcriptional regulatory factors to which it belongs .…”
Section: Discussionsupporting
confidence: 69%
“…We therefore propose that the glucose-sensing transcription factor MLX and myokine signaling may encompass a novel part of the molecular pathway necessary for glucose-induced adaptive myogenesis. Given its widespread expression, MLX may modulate the transcription of secreted signaling proteins in response to glucose in many cell types, which was also implicated by a recent study in colorectal cancer cells (Nam et al 2015). Therefore, our study indicates that MLX has more diverse roles than previously anticipated, presumably in concert with the large network of positive and negative transcriptional regulatory factors to which it belongs .…”
Section: Discussionsupporting
confidence: 69%
“…Amphiregulin plays an important role in pathological processes, including psoriasis induction , cancer progression, and resistance to chemotherapy and anti‐EGFR therapies . For example, AREG has been characterized as a multicrine – autocrine, paracrine, and endocrine (systemic) – growth factor in primary and metastatic epithelial cancers .…”
Section: Discussionmentioning
confidence: 99%
“…Results of in vivo studies implicate ADAM17 as the specific metalloprotease contributing to the ectodomain shedding of AREG , a potent growth factor implicated in proliferative skin diseases, and primary and metastatic epithelial cancers . Moreover, results of in vitro studies have suggested ADAM17 as a key sheddase ; nevertheless, ADAM8‐, ADAM15‐, and batimastat (broad metalloprotease inhibitor)‐sensitive metalloproteases have also been implicated in AREG shedding in vitro .…”
mentioning
confidence: 99%
“…In CRC cells, the FIH-1 expression markedly decreased HIF1α mediated expression of GLUT1 and VEGF. The expression of GLUT1 in CRC was partly regulated by the Amphiregulin-EGFR pathway [31]. Amphiregulin may possibly transactivate EGFR and consequently induce HIF-1α, leading to tumor progression and activation of genes responsible for the Warburg effect [31].…”
Section: Hypoxia Inducible Factor (Hif)mentioning
confidence: 99%